2018
DOI: 10.1021/acsami.8b19048
|View full text |Cite|
|
Sign up to set email alerts
|

Smart Metal–Organic Framework-Based Nanoplatforms for Imaging-Guided Precise Chemotherapy

Abstract: Good biocompatibility, active tumor targeting, and stimulus-responsive release offer great opportunity for precise imaging-guided tumor treatment. However, the current strategies for the fabrication of smart theranostic platforms suffer from tedious synthesis processes. Here, we propose a universal and facile strategy for the fabrication of smart nanoscale metal− organic framework (NMOF)-based nanoplatforms for imagingguided precise chemotherapy. As a proof of concept, 5boronobenzene-1,3-dicarboxylic acid (BBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 58 publications
(93 reference statements)
0
60
0
Order By: Relevance
“…Recently, Yin and co‐workers reported a smart NMOF‐based theranostic system integrating CT, MRI, and FL to guide precise chemotherapy of cancer 54. The NMOFs were constructed by 5‐boronobenzene‐1,3‐dicarboxylic acid (BBDC) ligands and Gd/Yb metal nodes.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
“…Recently, Yin and co‐workers reported a smart NMOF‐based theranostic system integrating CT, MRI, and FL to guide precise chemotherapy of cancer 54. The NMOFs were constructed by 5‐boronobenzene‐1,3‐dicarboxylic acid (BBDC) ligands and Gd/Yb metal nodes.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
“…As degradable materials, the mechanism and metabolic processes of MOFs in the body need more data to understand. In recent years, a large number of studies on the in vitro cytotoxicity of MOFs have been reported [27,35,45,55,56,[58][59][60][61]77]. Although these data show that MOFs have good biosafety at a given dose, cell models do not demonstrate that they still display the same biocompatibility in the body.…”
Section: Toxicity and Biocompatibilitymentioning
confidence: 99%
“…It did not release in a neutral environment and released 75% of the drug within 24 h in a weak acid environment. In addition, DOX@MOFs-Glu was synthesized by Zhang and his colleagues who combined pH-responsive drugs, active targeting and CT imaging [55]. The glucose specifically recognized the glucose-transported protein (GLUT1) overexpressed on the surface of tumor cells.…”
Section: Multi-targeted Response Of Mof Nanomaterials For Anticancer Tmentioning
confidence: 99%
“…The MTT assay revealed that the DOX-loaded LA-modified NMOFs showed greater cytotoxicity towards HepG2 cells compared to normal HEK cells. Zhang et al 29 developed a novel strategy for the design of smart NMOFbased nanoplatforms for MRI-guided tumor-targeted precise chemotherapy. The glucose not only acted as a targeting ligand to glucose-transported proteins in cancer cells, but also endowed the NMOFs with a pH-responded release of DOX.…”
Section: Implication Of Nmofs In Chemotherapymentioning
confidence: 99%